2022
DOI: 10.1002/app.53009
|View full text |Cite
|
Sign up to set email alerts
|

Construction of antifouling and antibacterial polyhexamethylguanidine/chondroitin sulfate coating on polyurethane surface based on polydopamine rapid deposition

Abstract: Implanted medical devices are widely used in clinic for disease treatment, but they generally suffer from the bio‐fouling problem which leads to the reduction of service life and loss of therapeutic effects. Herein, an eco‐friendly method based on polydopamine (PDA) fast deposition is developed to construct anti‐fouling and antibacterial surface on polyurethane (PU). The self‐adhesive layer of PDA contributes to the formation of a platform with active sites for further antibacterial and hydrophilic modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…As shown in Figure and Table S2, after the modification of the PDA coating on PU, the N and O on the surface increased and the C decreased, which indicated that PDA was successfully grafted onto the surface. When PHMG was grafted onto the PDA surface, the O and N contents decreased and the C content increased compared to that of the PU-PDA coating, which indicated that PHMG was successfully grafted onto the PU-PDA surface . As shown in Figure a,b, the peak of Ag 3d appears on the surface of the PU-PDA-Ag coating because of the presence of AgNPs.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…As shown in Figure and Table S2, after the modification of the PDA coating on PU, the N and O on the surface increased and the C decreased, which indicated that PDA was successfully grafted onto the surface. When PHMG was grafted onto the PDA surface, the O and N contents decreased and the C content increased compared to that of the PU-PDA coating, which indicated that PHMG was successfully grafted onto the PU-PDA surface . As shown in Figure a,b, the peak of Ag 3d appears on the surface of the PU-PDA-Ag coating because of the presence of AgNPs.…”
Section: Resultsmentioning
confidence: 90%
“…As shown in Figure a, the untreated surface of PU was relatively smooth with some vein-like lines. After a layer of PDA was prepared on the surface, as shown in Figure b, the surface of PU-PDA was completely covered by PDA, and the vein-like lines disappeared . For the surface SEM of PU-PDA-Ag as shown in Figure c, a lot of silver nanoparticles that were reduced by PDA were attached to the surface.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations